2015
DOI: 10.1371/journal.pone.0120957
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy versus Isolation: A Qualitative Study of Sexual Practices among Sexually Active HIV-Infected Patients in HIV Care in Brazil, Thailand, and Zambia

Abstract: The success of global treatment as prevention (TasP) efforts for individuals living with HIV/AIDS (PLWHA) is dependent on successful implementation, and therefore the appropriate contribution of social and behavioral science to these efforts. Understanding the psychosocial context of condomless sex among PLWHA could shed light on effective points of intervention. HPTN 063 was an observational mixed-methods study of sexually active, in-care PLWHA in Thailand, Zambia, and Brazil as a foundation for integrating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…Fear of transmitting HIV, becoming pregnancy and a loss of sexual desire were also identified as barriers to sexual satisfaction for WLHIV post-HIV diagnosis [44,49,51]. These findings are supported by the results of recent studies conducted in African, European, South American, and Asian countries [80,81] that reported a lack of communication between WLHIV with their partner regarding safer and satisfying sexual practices led to sexual inactivity and dissatisfaction.…”
Section: Discussionsupporting
confidence: 52%
“…Fear of transmitting HIV, becoming pregnancy and a loss of sexual desire were also identified as barriers to sexual satisfaction for WLHIV post-HIV diagnosis [44,49,51]. These findings are supported by the results of recent studies conducted in African, European, South American, and Asian countries [80,81] that reported a lack of communication between WLHIV with their partner regarding safer and satisfying sexual practices led to sexual inactivity and dissatisfaction.…”
Section: Discussionsupporting
confidence: 52%
“…A total of 80 participants were included in the qualitative portion of the study [21] and included mixed sexual orientation and gender identity (see Table 1). Recruitment for this qualitative portion of HPTN 063 was voluntary.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Sample characteristics of the current sample (who commented on the role of alcohol) compared to the total qualitative sample are presented in Table 1. Additional information and procedures regarding the qualitative parent study are reported elsewhere [21].…”
Section: Data Collectionmentioning
confidence: 99%
“…This potential consequence is likely not only to affect women's willingness to disclose their HIV status, but also to compromise their safety due to threats or experience of violence. Some women living with HIV report rejection of sexual relations by their partners or inability to find sexual partners because of their HIV status [ 18 , 71 ]. Women living with HIV may also experience internalized stigma that includes fear and anxiety that partners may not find them attractive [ 70 , 72 , 73 ].…”
Section: Stigma and Discriminationmentioning
confidence: 99%